Cerebrospinal fluid corticosteroid levels and cortisol metabolism in patients with idiopathic intracranial hypertension: a link between 11beta-HSD1 and intracranial pressure regulation? - Sinclair, A; Walker, E; Burdon, M; van Beek, A; Kema, I; Hughes, B; Murray, P; Nightingale, P; Stewart, P; Rauz, S; Tomlinson, J (2010)
CONTEXT: The etiology of idiopathic intracranial hypertension (IIH) is unknown. We hypothesized that obesity and elevated intracranial pressure may be linked through increased 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) activity. OBJECTIVE: The aim was to characterize 11β-HSD1 in human cerebrospinal fluid (CSF) secretory [choroid plexus (CP)] and drainage [arachnoid granulation tissue (AGT)] structures, and to evaluate 11β-HSD1 activity after therapeutic weight loss in IIH. DESIGN AND SETTING: We conducted in vitro analysis of CP and AGT and a prospective in vivo cohort study set in two tertiary care centers. PATIENTS OR OTHER PARTICIPANTS: Twenty-five obese adult female patients with active IIH were studied, and 22 completed the study. INTERVENTION: Fasted serum, CSF, and 24-h urine samples were collected at baseline, after 3-month observation, and after a 3-month diet. MAIN OUTCOME MEASURES: Changes in urine, serum, and CSF glucocorticoids (measured by gas chromatography/mass spectrometry and liquid chromatography/tandem mass spectrometry) after weight loss were measured. RESULTS: 11β-HSD1 and key elements of the glucocorticoid signaling pathway were expressed in CP and AGT. After weight loss (14.2±7.8 kg; P<0.001), global 11β-HSD1 activity decreased (P=0.001) and correlated with reduction in intracranial pressure (r=0.504; P=0.028). CSF and serum glucocorticoids remained stable, although the change in CSF cortisone levels correlated with weight loss (r=-0.512; P=0.018). CONCLUSIONS: Therapeutic weight loss in IIH is associated with a reduction in global 11β-HSD1 activity. Elevated 11β-HSD1 may represent a pathogenic mechanism in IIH, potentially via manipulation of CSF dynamics at the CP and AGT. Although further clarification of the functional role of 11β-HSD1 in IIH is needed, our results suggest that 11β-HSD1 inhibition may have therapeutic potential in IIH.